2022
DOI: 10.3390/cells11050765
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Acylation—A Post-Translational Tuning Mechanism Regulating Adult Hippocampal Neurogenesis

Abstract: Adult hippocampal neurogenesis—the generation of new functional neurones in the adult brain—is impaired in aging and many neurodegenerative disorders. We recently showed that the acylated version of the gut hormone ghrelin (acyl-ghrelin) stimulates adult hippocampal neurogenesis while the unacylated form of ghrelin inhibits it, thus demonstrating a previously unknown function of unacyl-ghrelin in modulating hippocampal plasticity. Analysis of plasma samples from Parkinson’s disease patients with dementia demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…The enzyme that catalyzes the octanoylation of ghrelin is ghrelin O-acyltransferase (GOAT), a member of the family membrane-bound O-acyl transferase (MBOAT). Octanoylation is achieved by attaching an eight-carbon medium-chain fatty acid (MCFA) (octanoate) to serine 3 of ghrelin [ 4 , 5 ] ( Figure 1 ). Ghrelin is the only peptide hormone in mammals that is acylated, which is crucial for its binding to GHS-R1a [ 6 ].…”
Section: Ghrelin Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme that catalyzes the octanoylation of ghrelin is ghrelin O-acyltransferase (GOAT), a member of the family membrane-bound O-acyl transferase (MBOAT). Octanoylation is achieved by attaching an eight-carbon medium-chain fatty acid (MCFA) (octanoate) to serine 3 of ghrelin [ 4 , 5 ] ( Figure 1 ). Ghrelin is the only peptide hormone in mammals that is acylated, which is crucial for its binding to GHS-R1a [ 6 ].…”
Section: Ghrelin Characteristicsmentioning
confidence: 99%
“…In depressed patients, these inverse correlations are also seen. Faecalibacterium [ 3 ] and Prevotellaceae [ 4 ] levels are reduced in patients with depression. Changes in the Bacteroidetes/Firmicutes ratio may also promote depression [ 5 ].…”
Section: Ghrelin and The Microbiota And Its Link To Immunometabolic D...mentioning
confidence: 99%
“…The precise mechanisms by which acyl‐ghrelin signalling mediates AHN remain unclear; however, this may be via non‐cell autonomous pathways involving the release of pro‐neurogenic factors (Buntwal et al , 2019; Sassi et al , 2022). More recently, we showed that acyl‐ghrelin increased BDNF mRNA—a neurotrophic factor—within the granule cell layer of the hippocampus (Hornsby et al , 2020).…”
Section: Introductionmentioning
confidence: 99%